If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + 7 + -1 = 6 Reorder the terms: 7 + -1 + r = 6 Combine like terms: 7 + -1 = 6 6 + r = 6 Add '-6' to each side of the equation. 6 + -6 + r = 6 + -6 Combine like terms: 6 + -6 = 0 0 + r = 6 + -6 r = 6 + -6 Combine like terms: 6 + -6 = 0 r = 0 Solving r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Simplifying r = 0
| 0.7=x-1.2x | | b/5-9=-1 | | 9000=.07*1*x | | 43=-7+5x | | 3ln(3x-4x^3)=0 | | X+2y=195 | | x*y=24 | | 2.8=ln(y) | | 9000=.05*1*x | | 6x-6x+9=9 | | 15=1+6a+a | | 15x+5=135 | | 1+5p+8p=1 | | x+y=39 | | 6r-5r=-7 | | 1x+2y=49 | | -9=c/12 | | 98=6+34 | | 5=7v+8+4 | | Ln(8x+2)=Ln(4x-10) | | 50/5= | | 12x+5x+7=9 | | -6=k-8-1 | | 4(3-5x)=3(-3x+15) | | 4/x=2/11 | | 10x-3=7x-11 | | 10/2= | | 13=-7p-6p | | a^2-9=40 | | x/5=6/2 | | 5x+11=3+8x-7 | | x-11=-7 |